Faktor-Faktor yang Memengaruhi Minat Mahasiswa Akuntansi Universitas Negeri Jakarta untuk Mengikuti Ujian Chartered Accountant - Amelia, Adien; Zakaria, Adam; Utaminingtyas, Tri Hesti (Jurnal Akuntansi, Perpajakan dan Auditing, 2024)
The purpose of this research is to determine factors that influence the interest of accounting students at State University of Jakarta to take the chartered accountant exam and this research was conducted on active students of the undergraduate accounting study program. The sample in this study were 107 students with the method which is determining the sample using purposive sampling. Research data which collected was carried out by distributing google form questionnaires to the population. Data analysis technique that used is multiple linear regression analysis. The results of the analysis is show that Quality Motivation affects student interest in taking the CA Exam, Reward/Recognition motivation affects students' interest in taking the CA Exam, and Labor Market Considerations affect student interest in taking the CA Exam.